Affective Atmosphere in an Art Fair Jewel Heist - Yates, Donna (European journal on criminal policy and research, 2025)
In mid 2022, social media videos of an armed jewel heist during opening hours at the TEFAF art fair baffled the public. The thieves wore seemingly absurd costumes, and the art fair attendees only showed muted reactions to a violent and dramatic crime. Drawing on first-hand observational research at TEFAF before and after the heist, and on an extended observational methodology focused on the atmosphere of art commercial spaces, we argue that the affective atmosphere of the art fair had a direct influence both on how the thieves committed and how onlookers experienced crime. Within the art fair space, thieves conformed to art world conventions and fair attendees experienced dangerous events as being significantly less sinister. With this paper, we contribute to the growing concept of sensory criminology and the role that atmosphere and affect play in crime.